CHRONIC EFFECT OF HYDROGYM IN PEOPLE WITH OBESITY AND CNCD POST-COVID: A PILOT STUDY - Aparecida de Souza, Andressa; Gabriel da Silva Alexandrino, Wesley; Regina de Sousa, Thais; Jane dos Santos Pascoini, Mara; Faúndez Casanova, César; Nardo Junior, Nelson (Arquivos do Mudi, 2023)
The objective of this study is to verify the effec of the practice of Hydrogymnastics as a regulatory factor for the treatment of obesity and post-COVID CNCDs. This is a descriptive research with a comparative approach, carried out with individuals with obesity. A 16-week Intervention program was applied, in which 40 volunteers participated, who were assigned to an Intervention Group (IG) and a Comparison Group (CG). The analysis was descriptive between pre and post test (GI= 26 and GC=14). Normality was contrasted for the total sample, and by group (G1 and G2) for each of the measured variables. In the intervention group, some variables were maintained and did not change significantly, there were improvements only in DBP and HR. In the CG there were improvements only in the HR variable, they also obtained improvements in weight, BMI, DBP and SBP, with a small effect size. The Hydrogymnastic Training Program, performed in adults with obesity, in this study showed an improvement in the response of the double product: heart rate and systolic blood pressure.